THE SYSTEMATIZATION OF RAILWAY WHEELS DEFECTS - Gryshchenko, M. A. (Science and Transport Progress, 2008)
In the article the research results of occurring defects in railroad wheels, the systematization and attempt of explaining the causes of occurring them are presented.